1993
DOI: 10.1063/1.109485
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen enhancement of silicon thermal donor formation

Abstract: Oxygen-related thermal donor formation in Czochralski silicon is characterized by the capacitance-voltage and deep level transient spectroscopy techniques as a function of 450 °C anneal time following hydrogenation. Increases in the formation rate and number of thermal donor (TD) defects found after hydrogenation are reported. This study finds an increase in TD+/++ concentration in the near-surface region at short anneal times, but at longer times an elevated concentration was not observed. No acceleration thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In the latter case, it is known that H accelerates interstitial oxygen diffusion, 2 resulting in a faster oxygen thermal donor ͑TD͒ ͑OTD͒ formation. [3][4][5][6] At the same time, hydrogen-related shallow TDs ͑STDHs͒ have also been observed, [7][8][9][10][11][12][13] with ionization energies in the range of 35-40 meV and infrared absorption peaks in the sub-300 cm −1 wavenumber range. These centers can be exploited for the low temperature formation of deep p-n junctions in p-type CZ silicon.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…In the latter case, it is known that H accelerates interstitial oxygen diffusion, 2 resulting in a faster oxygen thermal donor ͑TD͒ ͑OTD͒ formation. [3][4][5][6] At the same time, hydrogen-related shallow TDs ͑STDHs͒ have also been observed, [7][8][9][10][11][12][13] with ionization energies in the range of 35-40 meV and infrared absorption peaks in the sub-300 cm −1 wavenumber range. These centers can be exploited for the low temperature formation of deep p-n junctions in p-type CZ silicon.…”
mentioning
confidence: 73%
“…2 and 3 is that hydrogen enhances the transport of interstitial oxygen, resulting in an accelerated OTD formation. [2][3][4][5][6] Figure 3 should then represent the increase of the oxygen diffusion coefficient, provided hydrogen does not interfere with the oxygen clustering process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, hydrogen can also activate otherwise electrically neutral impurities, like carbon in silicon [1][2][3] or it plays a catalytic role in certain defect formation processes. A good example of the latter case is the generation of oxygen thermal donors (OTDs) in Si in the temperature range between 300 and 500 • C [4][5][6][7]. It has been shown that doping Czochralski (Cz) silicon with hydrogen enhances the introduction rate of OTDs, typically by a factor 5-10 for a 450 • C annealing temperature, compared with no hydrogen doping [4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high reactivity and mobility, hydrogen interacts with other impurities, either passivating harmful generation-recombination centers and dopants, like B and P or activating neutral impurities, like carbon and oxygen. In the latter case, it is known that H accelerates the oxygen diffusion [2], resulting in a faster oxygen thermal donor (OTD) formation [3][4][5][6]. At the same time, hydrogen-related Shallow TDs (STDHs) have also been observed [7][8][9][10][11][12][13], with ionization energies in the range 35-40 meV and infrared absorption peaks in the sub 300 cm -1 range typically.…”
Section: Introductionmentioning
confidence: 99%